Diabetes Care in Malaysia: Problems, New Models, and Solutions - Zanariah Hussein; Sri Wahyu Taher; Harvinder Kaur Gilcharan Singh; Winnie Chee Siew Swee (Ubiquity Press, 2016)
Background: Diabetes is a major public health concern in Malaysia, and the prevalence of type 2 diabetes(T2D) has escalated to 20.8% in adults above the age of 30, affecting 2.8 million individuals. The burden of managing diabetes falls on primary and tertiary health care providersoperating in various settings. Objectives: This review focuses on the current status of diabetes in Malaysia, including epidemiology, complications, lifestyle, and pharmacologic treatments, as well as the use of technologies in its management and the adoption of the World Health Organization chronic care model in primary care clinics. Methods: A narrative review based on local available health care data, publications, and observations from clinic experience. Findings: The prevalence of diabetes varies among the major ethnic groups in Malaysia, with Asian Indians having the highest prevalence of T2D, followed by Malays and Chinese. The increase prevalence of overweight and obesity has accompanied the rise in T2D. Multidisciplinary care is available in tertiary and primary care settings with integration of pharmacotherapy, diet, and lifestyle changes. Poor dietary adherence, high consumption of carbohydrates, and sedentary lifestyle are prevalent in patients with T2D. The latest medication options are available with increasing use of intensive insulin regimens, insulin pumps, and continuous glucose monitoring systems for managing glycemic control. A stepwise approach is proposed to expand the chronic care model into an Innovative Care for Chronic Conditions framework to facilitate implementation and realize better outcomes in primary care settings. Conclusions: A comprehensive strategy and approach has been established by the Malaysian government to improve prevention, treatment, and control of diabetes as an urgent response to this growing chronic disease.